What's for Lunch? Investigating the Experiences, Perceptions, and Habits of Parents and School Lunches: A Scoping Review. (20th August 2020) - O'Rourke, Brianne; Shwed, Alanna; Bruner, Brenda; Ferguson, Kristen
ABSTRACT: BACKGROUND: Research indicates home‐packed school lunches are lower in nutritional value compared with school‐provided meals. Due to the lack of a school lunch program, most of what Canadian children consume during the school day is determined by parents and caregivers through packed lunches. Despite this, little research has focused on the school lunch packing habits and attitudes of parents. The purpose of this scoping review was to improve understanding of parental perceptions, experiences, and habits with respect to home‐packed school lunches. METHODS: We conducted a scoping review of peer‐reviewed and gray literature. We reviewed only studies published from January 2000 to January 2019 with a focus on parents' lunch packing habits for their school‐aged children. RESULTS: The review included 7 studies, with articles from the United Kingdom, Australia, and Canada. The studies identified 6 themes influencing parental decisions regarding what to pack in their child's lunch—school environment, food as fuel, convenience, child's influence, cost, and the lunch experience. CONCLUSIONS: The decisions that influence what is packed in a school lunch are complex and indicate the need for support. Parents, schools, districts, and government policymakers need to work collaboratively to improve the healthiness of home‐packed school lunches.